Molecular Mechanism for Cellular Response to β-Escin and Its Therapeutic Implications - Domanski, Dominik; Zegrocka-Stendel, Oliwia; Perzanowska, Anna; Dutkiewicz, Malgorzata; Kowalewska, Magdalena; Grabowska, Iwona; Maciejko, Dorota; Fogtman, Anna; Dadlez, Michal; Koziak, Katarzyna (PLOS ONE, 2016)
β-escin is a mixture of triterpene saponins isolated from the horse chestnut seeds (Aesculus hippocastanum L.). The anti-edematous, anti-inflammatory and venotonic properties of β-escin have been the most extensively clinically investigated effects of this plant-based drug and randomized controlled trials have proved the efficacy of β-escin for the treatment of chronic venous insufficiency. However, despite the clinical recognition of the drug its pharmacological mechanism of action still remains largely elusive. To determine the cellular and molecular basis for the therapeutic effectiveness of β-escin we performed discovery and targeted proteomic analyses and in vitro evaluation of cellular and molecular responses in human endothelial cells under inflammatory conditions. Our results demonstrate that in endothelial cells β-escin potently induces cholesterol synthesis which is rapidly followed with marked fall in actin cytoskeleton integrity. The concomitant changes in cell functioning result in a significantly diminished responses to TNF-α stimulation. These include reduced migration, alleviated endothelial monolayer permeability, and inhibition of NFκB signal transduction leading to down-expression of TNF-α—induced effector proteins. Moreover, the study provides evidence for novel therapeutic potential of β-escin beyond the current vascular indications.